Failure Analysis of LP Turbine Final Stage Blades of High Capacity Power Plants - Thiyagarajan, V.S.; Ananth Vino, V. Jose (International Journal of Psychosocial Rehabilitation, 2019)
Main steam turbines in an high capacity thermal power plants are vital and complicated fine aligned, coupled as single tandem high speed rotating mechanical equipment with very fine clearances. Failure analysis cause study on the LP Turbine final stage blades of high capacity Thermal Power Plant in Tamil nadu, india. The LP Turbine blades are made up of X20Cr35 alloy steel with FIR tree root. The study focuses on the LP turbine final stage blade failure for material degradation, Corrosion fatigue, High cycle fatigue and the type of corrosion mechanism which initiates the crack such as corrosion crack, stress corrosion crack, pitting corrosion cracks due to chlorine corrosion etc., Sediments of Silica and Chlorine were identified in Turbine rotor and stator blade trailing edges, Corrosion pitting were identified along the LP Turbine blade trailing edges. The study further focuses on various operating parameters and history of events to arrive optimum solution.